2006
DOI: 10.1097/00000542-200608000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of Gray and White Matter Injury after Spinal Cord Ischemia in Rabbits

Abstract: The results in the current study show that SCI induced white matter injury as well as gray matter injury in a rabbit model of SCI. The time course for 14 days after reperfusion may differ among the gray and white matter damages and hind-limb motor function in rabbits subjected to SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…In the present study, a rabbit model of SCI was used due to the following reasons. First, in a rat SCI model, it has been reported that motor function gradually improved without no delayed deterioration, while hind-limb motor function deteriorated after SCI over 2 weeks in a rabbit model (21). Delayed development of paraplegia is well known in human, so that the time course after SCI in human may resemble to that in rabbit.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a rabbit model of SCI was used due to the following reasons. First, in a rat SCI model, it has been reported that motor function gradually improved without no delayed deterioration, while hind-limb motor function deteriorated after SCI over 2 weeks in a rabbit model (21). Delayed development of paraplegia is well known in human, so that the time course after SCI in human may resemble to that in rabbit.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we cannot conclude about the neuroprotective effect of xenon on white matter injury because white matter injury may not appear within 48 h after reperfusion. Kurita et al 23 reported that white matter injury after spinal cord ischemia did not appear 24 h after reperfusion, but was apparent 4 days after reperfusion in rabbits. Longer recovery periods might be necessary for the assessments of white matter injury.…”
Section: Discussionmentioning
confidence: 99%
“…The vacuolation indicates a segmental swelling of myelinated axons, the formation of spaces between myelin sheaths and axolemma, and astrocyte swelling (Kurita et al, 2006). APP is transported by fast anterograde axonal transport; therefore, the accumulation of APP at the sites of injury, accompanied by morphologic evidence of axonal damage in the form of axonal swelling or bulbs, has been regarded as evidence of axonal injury (Kurita et al, 2006). Our data demonstrate that combination of IPC and postconditioning attenuated white matter injury as well as gray matter injury resulting from spinal cord ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…The percent area of vacuolation of the three target areas was calculated and the data were then averaged (Kurita et al, 2006).…”
Section: Histological Studymentioning
confidence: 99%
See 1 more Smart Citation